Length‐weight relationships for 11 fish species from the tributary of Amur River (Fuyuan, NE China). (7th October 2013) - Huang, P. Y.; Jia, M. Y.; Chai, L. H.; Yu, H. X.; Yu, X. D.; Wu, Zh. F.
Summary Length‐weight relationships were determined for 11 fish species from the tributary of Amur River in Fuyuan, northeastern China. This is the first record of length‐weight relationships for six of these species.